Outsourcing in health care sector: a state of the art review - Guimarães, M.; Crespo de Carvalho, J. (Supply Chain Forum: An International Journal, 2011)
Outsourcing has become one of the healthcare sector’s buzzwords. In the supply chain management of healthcare organizations, outsourcing decisions have specific distinctiveness. This article reviews the state-of-the- art literature on outsourcing in the healthcare sector and provides a structured frame of outsourcing in different countries with different healthcare systems. This appears to be the first time evidence on outsourcing practices in the healthcare sector have been systematically collected and structured in order to understand the reality beyond the outsourcing processes and trends.